PERAN PENGGUNAAN IT (INFORMATION AND TECHNOLOGY) DAN KOMPETENSI TERHADAP KINERJA PADA TENAGA KEPENDIDIKAN UNIVERSITAS SEMARANG DENGAN MOTIVASI PRESTASI SEBAGAI INTERVENING - Ahmad Isyabul Izzi; Indarto; Djoko Santoso (Universitas Semarang, 2025)
This study aims to analyze the effect of the use of information technology and competence on the performance of educational personnel with achievement motivation as an intervening factor. The problem behind this study is to analyze the responsiveness aspect or the quick response of educational personnel (tendik) at Semarang University who have a lower job satisfaction assessment ratio compared to other aspects. This indicates that the performance of Educational Personnel at Semarang University in handling lecturer and student problems still needs to be improved and encourages Educational Personnel to make more use of information technology at Semarang University and improve competence in accordance with their respective main tasks through achievement motivation so that it can affect the performance of Educational Personnel. This research is a quantitative research with an explanatory approach. It utilizes primary data, obtained directly from the research subjects through questionnaires. The study was conducted at the University of Semarang, with a sample of 72 education personnel using proportional area sampling and proportional stratified random sampling. The analysis method used was the three-box method and PLS-SEM. The results of the analysis prove that competence has a positive effect on the performance of educational staff, the use of information technology does not have a positive effect on the performance of educational staff, competence has a positive effect on achievement motivation, the use of information technology has a positive effect on achievement motivation, achievement motivation has a positive effect on the performance of educational staff and achievement motivation can mediate the influence of competence and the use of information technology on the performance of educational staff.